Fenofibrate-induced decrease of expression of CYP2C11 and CYP2C6 in rat - Večeřa, Rostislav; Zachařová, Alice; Orolin, Jan; Strojil, Jan; Skottová, Nina; Anzenbacher, Pavel (Biopharmaceutics & drug disposition, 2011)
This short communication is aimed to investigate whether the widely used hypolipidemic drug fenofibrate affects CYP2C11 and CYP2C6 in rats, both counterparts of human CYP2C9, known to metabolise many drugs including S-warfarin and largely used non-steroidal antiinflammatory drugs such as ibuprofen, diclofenac and others. The effects of fenofibrate on the expression of rat liver CYP2C11 and CYP2C6 were studied in both healthy Wistar rats and hereditary hypertriglyceridemic rats. Both strains of rats were fed on diet containing fenofibrate (0.1% w/w) for 20 days. Fenofibrate highly significantly suppressed the expression of mRNA of CYP2C11 and less that of CYP2C6 in liver microsomes of both rat strains; this effect was associated with a corresponding decrease in protein levels. The results indicate that the combination of fenofibrate with drugs metabolised by CYP2C9 in humans should be taken with caution as it may lead, for example, to the potentiation of warfarin effects. This type of drug interaction has been observed previously and the results presented here could contribute to the explanation of their mechanism.
Keywords: Microsomes, Liver; Cytochrome P450 Family 2; Male; steroid-16-alfa-hydroxylasa; steroid-21-hydroxylasa; Rats, Wistar; hypertriglyceridemie; Fenofibrate; Hypertriglyceridemia; rodina 2 cytochromů P450; mužské pohlaví; potkani Wistar; Enzyme Repression; krysa rodu Rattus; Animals; Hypolipidemic Agents; aromatické hydroxylasy; Aryl Hydrocarbon Hydroxylases; zvířata; Rats; hypolipidemika; Steroid 16-alpha-Hydroxylase; enzymová represe; Steroid 21-Hydroxylase; fenofibrát; jaterní mikrozomy